Predicting public support: applying theory to prosocial behaviors. Issue 4 (6th August 2019) - McKeever, Brooke W.; McKeever, Robert; Pressgrove, Geah; Overton, Holly
Abstract : Purpose: The purpose of this paper is to apply communication theory to explore and help explain public support for causes and organizations in the form of prosocial behaviors, including donating, volunteering and participating in advocacy efforts. Design/methodology/approach: Through a survey of people ( n =1, 275) living in the USA who indicated supporting issues they cared about in 2017, this research gathered information about motivations for providing public support for various causes and non-profit organizations. Findings: The situational theory of problem solving (STOPS) was applied, and support was found for the STOPS model in terms of predicting communicative action. This study also found support for situational activeness influencing other behaviors, including active forms of communication, financial support, volunteer support and other forms of advocacy. Implications for practitioners managing communications or organizations involved in such efforts are discussed. Originality/value: This research applied STOPS to study behaviors, including communication, volunteering, donating and participating in advocacy efforts as forms of prosocial behavior supporting different organizations related to many important issues. The paper provides theoretical value in terms of adding to the generalizability of the STOPS model for communications scholars and discusses practical implications for non-profit and other types of organizations.